The Effect of Ownership Structure, Profitability, Leverage, and Firm Size on Corporate Social Responsibility (CSR) - Fifi Swandari; Ali Sadikin (Binus Business Review, 2016)
Corporate Social Responsibility (CSR), indicator used was the index of CSR disclosure with 64 companies listed in Indonesia Stock Exchange period of 2012 as the samples. This research used multiple regression analysis. The results show that institutional ownership, managerial and foreign has no effect on CSR. This indicates that the ownership structure could not improve CSR in the company. On the contrary, profitability has an influence on CSR. It indicates that companies with high profits have the fund flexibility to implement CSR programs that have been set. Moreover, corporate debt levels also affect the CSR with the negative direction. This means that companies with high debt levels will usually focus more on managing faced business risks rather than on CSR program. Last, company size has no effect on the company CSR.